Polyglot software development: wait, what? - Mussbacher, Gunter; Combemale, Benoit; Kienzle, Jörg; Burgueño-Caballero, Lola; Garcia-Dominguez, Antonio; Jézéquel, Jean-Marc; Jouneaux, Gwendal; Khelladi, Djamel-Eddine; Mosser, Sébastien; Pulgar, Corinne; Sahraoui, Houari; Schiedermeier, Maximilian; et al. (IEEE, 2024)
We propose a concise and unambiguous definition of polyglot software development with a conceptual model and characterize the techniques used for the specification and operationalization of polyglot software development with a feature model.
Keywords: Lenguajes de programación; Soporte lógico - Desarrollo; Task analysis; Stakeholders; Codes; Programming; Unified modeling language; Programming profession; Software development management; Product development; Multilingual; Software development; Operationalized; Conceptual model; Salbutamol; Continuous Integration; Definition of development; Structured query language; Domain specific languages; Language combinations; Active involvement; Technical challenges; Interoperability; Application programming interface; Transformer model; Educational challenges; Multiple languages; Object oriented; Python programming; Integration of techniques; Role of stakeholders; Composite technique; Shared memory; Single language; Work unit; Partial order; Task definition